The Office of Religious Affairs' Role in Combating Siri Marriage in Sambi Rampas District, East Manggarai Regency - Ahmad Muntazhar; Ramadhan Saha (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2022)
The purpose of this research is to find out: 1) how unregistered marriages are implemented in Sambi Rampas District, East Manggarai Regency; and 2) what the role of the Office of Religious Affairs is in dealing with unregistered marriages in Sambi Rampas District, East Manggarai Regency. This study is a qualitative descriptive one. Primary data were obtained by going directly to the field for interviews and observations, and secondary data were obtained by reviewing several literatures related to the title of the thesis. Following the collection of data, the next step is to process, analyze, and draw conclusions. The findings revealed that: 1) the implementation of unregistered marriages in Sambi Rampas District, East Manggarai Regency was caused by a number of factors, including: a lack of community economic factors, a low level of education, and a lack of legal knowledge and understanding of the importance of registering marriages. 2) The role of the Office of Religious Affairs in dealing with unregistered marriages in Sambi Rampas District, East Manggarai Regency, including: counseling prospective brides and guardians on marriage registration and happy families, as well as socializing the importance of marriage registration and its negative impact on families, mothers, and children through seminars and recitations held by the ministry of religion through representatives in the sub-district.–Penelitian ini bertujuan untuk mengetahui: 1) Bagaimana pelaksanaan nikah siri di Kecamatan Sambi Rampas Kabupaten Manggarai Timur; 2) Bagaimana peran Kantor Urusan Agama dalam mengatasi nikah siri di Kecamatan Sambi Rampas Kabupaten Manggarai Timur. Penelitian ini merupakan penelitian deskriptif kualitatif. Data yang diperoleh yaitu data primer yang didapat melalui terjun langsung ke lapangan untuk wawancara dan observasi, serta data sekunder yang diperoleh dengan pengkajian beberapa literatur yang berhubungan dengan judul skripsi. Setelah data terkumpul, Langkah selanjutnya adalah mengolah, menganalisis serta mengambil kesimpulan. Hasil penelitian menunjukan bahwa: 1) pelaksanaan nikah siri yang terjadi di Kecamatan Sambi Rampas Kabupaten Manggarai Timur disebabkan karna beberapa faktor, diantaranya: faktor ekonomi masyarakat yang minim, rendahnya tingkat pendidikan dan kurangnya pengetahuan dan pemahaman hukum tentang pentingnya pencatatan nikah. 2) peran Kantor Urusan Agama dalam mengatasi nikah siri di Kecamatan Sambi Rampas Kabupaten Manggarai Timur, diantaranya: melakukan penyuluhan-penyuluhan tentang pencatatan nikah dan keluarga bahagia kepada calon pengantin dan wali, serta melakukan sosialisasi tentang pentingnya pencatatan nikah dan dampak buruknya terhadap keluarga, ibu dan anak melalui seminar-seminar dan pengajian yang diadakan oleh departemen agama melalui perwakilan di Kecamatan yang diselenggarakan di masyarakat.